Evaluation of the Use of Antibiotics Using the ATC/DDD Method in Post-Surgery Patients at the Inpatient Installation of dr. Hospital. Zainal Umar Sidiki - Noviyanti I. Panu; Sarini Pani; Rini Daud Supu (Journal of Health, Technology and Science (JHTS), 2021)
In general, the use of antibiotics in health care facilities is more widely used in hospitals, especially in post-surgical patients. Infections that often appear in post-surgical patients are surgical wound infections. Surgical wound infection (ILO) is an infection in the incision area or organ-space that occurs in patients after surgery. Antibiotics are the most widely used drug class in the world due to the high incidence of bacterial infections. One of the most common is resistance to antibiotics. The purpose of this research To determine the use of antibiotics in post-surgical patients in the inpatient installation of RSUD dr. Zainal Umar Sidiki. Evaluation the use of antibiotics was assessed using the Defined Daily Dose (DDD)/100 bed-days and 90% DU segment. The results of the evaluation showed that the most widely used antibiotic was ceftriaxone with a value of 27.54 DDD/100 bed-days and quantitative use of antibiotics in post-surgical patients at RSUD dr. Zainal Umar Sidki is 69.77 DDD/100 bed-days and antibiotics that fall into the 90% DU segment are ceftriaxone, cefadroxil, cefixime and ciprofloxacin. While those included in the 10% DU segment were clindamycin, moxifloxacin hcl, cefotaxime, amoxicillin and azythromicin.